Transitioning from a Multi-Agency to an Integrated Food Control System: A Case Study from the Sultanate of Oman - Moza Abdullah Al Busaidi; Mohammad Shafiur Rahman; Hussein Samh Al Masroori (Foods)
Food safety regulations and their implementations are becoming increasingly complex due to various reasons such as diverse food sources, supply chain, processing technologies, distribution systems and environmental concerns. Additionally, it is crucial to address diversified consumers and their preferences. To address these multifaceted challenges, adopting an integrated unified management system is essential. This review provides a comprehensive overview of the progressive food safety governance in the Sultanate of Oman. The country is transitioning from a multi-agency to an integrated food control management system. This integrated approach can enhance the coordination between different government agencies and other stakeholders, avoid duplication, identify required resources and ensure optimum use of the resources. The progress can enhance efficiency and effectiveness in managing food safety in Oman. It addresses the issues of the food safety management system, explores the legislative frameworks, risk-based assessment and their enforcement, and creates public awareness and required research for continuous improvement in food safety. This integration approach is expected to continue strengthening food safety governance in the country. Finally, future challenges in achieving food safety are envisioned, including new food sources and technologies, applications of artificial intelligence, and new sensors for quick identification of risks in foods.